CuTiO3 perovskite-type as an efficient catalyst for alkaline lignin depolymerization towards selective vanillin production - Shanmugam, Ratheeshkumar; Chan Basha, Arul; Kumar, Vinod; Shanmugam, Saravanan Ramiah; Sriariyanun, Malinee; Venkatachalam, Ponnusami (MDPI, 2026)
Lignin is one of the most abundant biopolymers in nature. The major challenge in lignin depolymerization lies in the formation of complex mixtures that require extensive downstream separation. Selective depolymerization strategies aim to overcome this limitation by promoting controlled bond cleavage while suppressing undesired secondary reactions. In this work, a series of rare-earth-free, perovskite-type mixed metal oxides with general compositions ZnxNi1–xTiO3 and CuyNi1–yTiO3 were synthesized and evaluated as heterogeneous catalysts for the base-catalyzed depolymerization of lignin. Among the investigated materials, CuTiO3 exhibited superior catalytic performance, enabling the formation of vanillin as the dominant monomer with high selectivity. The selected catalyst was further characterized using X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), and Brunauer–Emmett–Teller (BET) surface area analysis. The combined effects of key reaction parameters, including temperature, pressure, lignin-to-catalyst ratio, NaOH concentration, and reaction time, were systematically investigated using response surface methodology (RSM). Under the optimized conditions (154 °C, 0.3 MPa, lignin-to-catalyst ratio of 24.5:1, 10 mL of 0.5 M NaOH, and 12 h reaction time), a monomer yield of 11.5 ± 0.46% with ~81% GC-selectivity toward vanillin was achieved. These findings demonstrate that perovskite-type titanates can serve as robust and reusable catalysts.
This article belongs to the Special Issue Catalysis and New Energy Materials
Keywords: 3402 Inorganic Chemistry; 34 Chemical Sciences; 3406 Physical chemistry; 4004 Chemical engineering; 4018 Nanotechnology; lignin; selective lignin depolymerization; perovskite-type metal catalyst; vanillin